Sustainable Marketing Strategies and Their Influence on Consumer Preferences for Eco-Friendly Products in Indonesia: The Mediating Role of Environmental Awareness - Khuan, Hendri; Marnoto, Marnoto; Tapaningsih, Weni Indah Doktri Agus; Purwoko, Bambang (International Journal of Business, Law, and Education, 2024)
This research investigates the influence of sustainable marketing strategies on consumer preferences for eco-friendly products in Indonesia, with a focus on the mediating role of environmental awareness. Drawing upon a quantitative approach, data were collected from a diverse sample of 150 participants using purposive sampling techniques. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze the relationships between sustainable marketing strategies, environmental awareness, and consumer preferences. The results reveal significant positive relationships between sustainable marketing strategies and consumer preferences, as well as between environmental awareness and consumer preferences. Furthermore, environmental awareness was found to partially mediate the relationship between sustainable marketing strategies and consumer preferences. These findings underscore the importance of integrating sustainability principles into marketing strategies and fostering environmental awareness to promote eco-friendly consumption behaviors among Indonesian consumers.